Postoperative Delirium is Not Associated with Long-Term Decline in Activities of Daily Living or Mortality After Laryngectomy - Wang Y (Dove Medical Press, 2021)
Yiru Wang,* Weiwei Liu,* Kaizheng Chen, Xia Shen Department of Anesthesiology, Eye & ENT Hospital, Fudan University, Shanghai, 200031, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xia ShenDepartment of Anesthesiology, Eye & ENT Hospital, Fudan University, 83 Fenyang Road, Shanghai, 200031, People’s Republic of ChinaTel +8621-643771334Fax +8621-64373416Email zlsx@yahoo.comPurpose: To determine the relationships between postoperative delirium (POD) and postoperative activities of daily living (ADL) and mortality in patients undergoing laryngectomy. We hypothesized that POD would reduce postoperative ADL and increase postoperative mortality.Patients and Methods: The prospective study included older participants (age ≥ 65 y) undergoing total laryngectomy, partial laryngectomy, total laryngectomy plus neck dissection, or partial laryngectomy plus neck dissection under general anesthesia. The diagnosis of delirium was based on the Confusion Assessment Method algorithm, which was administered on postoperative days 1 through 6. ADL were evaluated using the Chinese version of the Index of ADL scale. Follow-up assessments of ADL and mortality were conducted 24 months after surgery.Results: Of 127 participants (aged 70.3 ± 4.1 y), 19 (15.0%) developed POD. POD was not associated with a decrease in ADL after laryngectomy (p=0.599) nor with an increase in postoperative mortality [3/19 (15.8%) vs 12/108 (11.1%), p=0.560, Log rank test]. However, longer surgery duration was significantly associated with worse overall survival (OR, 3.262; 95% CI, 1.261– 9.169, p=0.025).Conclusion: POD was not associated with long-term ADL or mortality after laryngectomy. Prolonged surgery was the only factor associated with a higher postoperative mortality rate.Keywords: laryngeal cancer, postoperative delirium, activities of daily living, outcome